Genetic identification and twins: the objection regarding monozygotic twins - Caspar, Philippe (Medicina e Morale, 1994)
The author starts from the observation that many of the present debates on the identification of the human embryo are about the so-called "objection regarding monozygotic twins". The objection mentioned concems a concept of the individuai connected to indivisibility, according to which the embryo is not an individuai from the moment of conception in that during the initial phase of development it is subject to a division into two identical twins. The author first outlines a historical-philosophical profile of the evaluation given to twins and their formation. After also examining the contributions of modem biology and particularly the research of Hans Driesch, the embryologist who observed twinning in sea-urchins within the realm of a biologica] philosophy that links up with Aristotelian philosophy, the enormous step forward taken by the question due to the advances in molecular genetics is reviewed. The author also carries out a criticai analysis of the "objection" and acknowledges that it is founded on an illicit application of Leibnizian metaphysics according to which individuai equals indivisible. In reality the concept of individual refers to indivisibility in itself which distinguishes it from any other individuai. The article concludes with a reference to the animation of twins: the division into two of a morula does not mean the division of the soul, so the animation of the twin does not proceed from the first embryo but each of them are pervaded by a single spirit.